2019
DOI: 10.12991/jrp.2019.162
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of three Scutellaria L. species from Turkey

Abstract: Plant-sourced antimicrobials are known for their therapeutic potency against multi-drug-resistant pathogens. The members of Scutellaria L. have been used to cure several diseases in East Asia, Europe, and North America. The genus Scutellaria belonging to Lamiaceae family is composed of around 360 species worldwide and 18 species in Turkey. In this study, 36 extracts prepared with different solvents from aerial parts and roots of S. salviifolia Benth., S. diffusa Benth. and S. pontica C. Koch were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
(12 reference statements)
2
11
1
Order By: Relevance
“…with values between 64-32 μg/ml. And totally they found higher antifungal activity than antibacterial, in accordance with our results [11].…”
Section: Antimicrobial Activity Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…with values between 64-32 μg/ml. And totally they found higher antifungal activity than antibacterial, in accordance with our results [11].…”
Section: Antimicrobial Activity Resultssupporting
confidence: 91%
“…MIC results of methanol extract varied between 12,5-25 mg/ml against E. coli, K. pneumoniae, S. enteritidis P. aeruginosa, S. aureus [27]. Arıtuluk et al (2019) found that aqueous, methanol and n-butanol extracts from roots and methanol and n-butanol extracts from aerial parts of S. salviifolia, S. diffusa and S. pontica and n-hexane extracts from root parts of S. diffusa showed low or no antibacterial activity (1024 μg/ml). Aqueous extracts from the aerial parts showed moderate activity with the values of 1024-512 μg/ml; chloroform, ethylacetate and n-hexane extracts of roots and aerial parts showed low to moderate or no activity with the values of 1024-256 μg/ml, 1024-256 μg/ml, 1024-256 μg/ml, respectively.…”
Section: Antimicrobial Activity Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The dried extracts were dissolved in water and partitioned with n -hexane, dichloromethane and ethyl acetate. Each fraction and the methanol extracts were evaporated under vacuum and stored at 4 °C [ 50 ].…”
Section: Methodsmentioning
confidence: 99%
“…Plants of the genus Scutellaria L. are widespread in Europe, North America, East Asia and are extensively used in traditional Chinese medicine (Shang et al, 2010). Flavonoids isolated from plants of the genus Scutellaria L. exhibit antitumor (Yu et al, 2007), hepatoprotective (Jang et al, 2003), antioxidant (Sauvage et al, 2010), anti-inflammatory (Dai et al, 2013), anticonvulsant (Park et al, 2007), antimicrobial (Arituluk et al, 2019) and antiviral activity (Leonova et al, 2020). The creation of drugs based on flavonoids is based on the establishment of the 'chemical structure-pharmacological properties' relationship, and the determination of the structure of a new flavonoid may become a key starting point.…”
Section: Chemical Contextmentioning
confidence: 99%